New In-situ Heating Apparatus Setup for Universal Testing Machine - Algarni, Mohammed (Makara Journal of Technology, 2022)
This paper presents a novel idea of establishing a low cost and highly efficient heating apparatus. This apparatus can be used along with any universal testing machines (UTM) for various tests, such as fracture, fatigue, torsion, and shear. This low cost and highly efficient option for researchers in solid mechanics may be used in a broad range of promising research areas. Moreover, this novel apparatus is beneficial for all researchers interested in high-temperature solid mechanics and applications. An extensive literature review presented reveals the existing heating apparatus currently used in mechanical testing labs globally, along with their pros and cons. A comparative study of the new heating apparatus and the current ones shows the advantages of the new heating apparatus and reveals how it overcomes the drawbacks of the existing heating apparatuses. The setup and connection of the new heating apparatus illustrate its secure operation and its easy commercial acquisition.